MCQ bar reviewer in political law, labor law, and tax law - The Philippine Association of Law Schools (PALS) (Quezon City, Philippines Central Book Supply, Inc., 2011)
Summary: The impetus behind the conception and realization of the Multiple Choice Question (MCQ) Bar Reviewer comes from a deep recognition of the effectiveness of the multiple choice type of questions as a better barometer of the knowledge and competence of a future member of the legal profession. It is a concrete and prompt respone of the Philippine Association of Law Schools to the challenge posed by the new innovation in the Bar Examinations which will be implemented for the first time in November, 2011. - - Excerpt from the Preface
Keywords: Law -- Philippines -- Examinations, questions, etc; Bar examinations -- Philippines -- Study guides